Carotid artery intima-media thickness and erectile dysfunction in patients with metabolic syndrome - Unal, Mustafa (International Scientific Literature, Inc., 2014)
BACKGROUND: Metabolic syndrome (MS) has become a pandemic in Turkey, as is the case globally. Increase in carotid artery intima-media thickness (CIMT) and erectile dysfunction (ED) may be evident before the clinical signs of cardiovascular disease appear. We aimed to investigate the prevalence of increased CIMT and ED as markers of atherosclerotic disease in patients with MS. MATERIAL/METHODS: Thirty-two patients with MS and 29 healthy controls were included. Anthropometric and biochemical parameters, along with total testosterone (TT), high sensitive C-reactive protein (hs-CRP), were recorded. Carotid artery intima-media thickness was measured. Erectile dysfunction was assessed with International Index of Erectile Function. RESULTS: Patients with MS had higher BMI, fasting plasma glucose, post-prandial plasma glucose, insulin, HOMA-IR, total cholesterol, triglycerides, hs-CRP, and CIMT, whereas TT levels were lower (p<0.0001). The prevalence and severity of erectile dysfunction were higher in patients with MS (p<0.0001). Erectile dysfunction scores correlated inversely with CIMT. MS patients with ED were older and had higher CIMT compared to those without ED. Increase in age and HOMA and decrease in TT increased the risk of ED. When KIMT exceeding the 95(th) percentile of healthy controls was accepted as a risk factor for CVD, presence of ED was the only determinant for this increase. CONCLUSIONS: Erectile dysfunction was more prevalent and severe in patients with MS and correlated with subclinical endothelial dysfunction. Total testosterone deficiency was prominent among MS patients. Presence of ED points to an increased risk of cardiovascular disease when MS is present.